Environmental consciousness among students - Mahlatsi, Bonolo Esther (University of the Free State, 2025)
Determining individuals’ levels of environmental consciousness is essential in research. Concern about the environment is growing because of the increasing environmental degradation caused by human activities. Environmental consciousness is a term that has become more popular in recent years as environmental problems, largely caused by human activities, have accelerated. Environmental consciousness is a multifaceted concept with four dimensions, including environmental attitude, knowledge, value, and motivation. Environmental consciousness also entails socio-economic and psychological factors relating to an individual’s propensity to engage in pro-environmental behaviour. It focuses on people’s understanding of the environment, its problems, and processes. The relationship between humans and the environment has been one-sided for centuries, which has resulted in overwhelming and irreparable damage to the environment and ecosystems. This damage is largely due to human consumption causing the vulnerability of social systems. Since environmental problems have escalated to a global agenda, society is starting to question its environmental attitudes and behaviours; there seems to be an attitude-behaviour gap that exists in society. Human consumption and the extinction of species are not considered to be pressing environmental issues, which is problematic. Therefore, engaging people about their environmental behaviour and attitudes towards the environment is essential. Previous studies on environmental consciousness have focused more on consumer behaviour rather than on students’ attitudes and awareness of environmental issues. Therefore, there is a gap in the literature about young people’s attitudes to the environment, their awareness of environmental issues, and their perceptions of environmental sustainability. This gap in the literature is especially true in the South African context. The scant research is evidence that students’ perceptions of environmental problems are not well-known. Furthermore, how students learn about the environment is not integrated into their primary or secondary schooling or even into higher education curricula. Indeed, understanding the environmental attitudes and behaviour of university students has become a salient topic at South African universities because environmental attitudes and behaviour play a key role in shaping students’ perceptions of the environment at large. Furthermore, many environmental actions taken today are not actually based on protecting the environment from the influence of human activity and consumption. Rather, protecting the environment is a key social and political issue. Therefore, this study aims to explore what South African students’ perceptions of the environment are and what their level of environmental consciousness is. The study also intends to investigate whether students are indifferent or ambivalent towards the environment and environmental issues and, if so, what the reasons behind this attitude are. The study employed a mixed methods approach embedded in a cross-sectional study. The researcher embedded methodological triangulation to cross-validate the findings of the study to provide a comprehensive analysis. The target population consisted of both undergraduate and postgraduate students. The population also consisted of students from all genders, ages, ethnic groups, and faculties. The random sample size consisted of 380 respondents (at a 95% confidence level and 5% confidence interval). To allow for an estimated sample mortality of 35%, a total sample size of 585 was decided upon. The sampling design was determined with the Simple Random Size calculator. There were two data collection phases. Phase one (the quantitative component embedded in an exploratory survey design) entailed the dissemination of an online survey. The online survey was administered to a sample of registered students at all three campuses of the University of the Free State (the Bloemfontein, South, and QwaQwa campuses). Phase two (the qualitative component involved inviting the respondents who had completed the online survey to participate in mini groups. A sequential explanatory approach was embedded in the data-gathering processes of both phases. The study adopted a six-step reflexive thematic analysis to examine the participants’ experiences and perceptions of environmental issues. Factor analysis was conducted to reduce the large dataset into a smaller one made up of fewer factors. Exploratory factor analysis was used in the early stages of the data analysis to explore the interrelationships between the set of variables contained in the study’s five scales. Furthermore, Cronbach’s alpha coefficients were measured to determine the reliability and validity of the items contained in the scales; only highly dependable coefficients with values between 0.80 and 1.00 were reported. There were 416 respondents who completed the online survey and nine participants who participated in the mini groups. The findings revealed that students had both anthropogenic and ecologically-minded worldviews; they also had mixed reactions to the environment and environmental issues and were either exemptionalists or ecologically-minded. The participants were aware of environmental issues and of their behaviour towards the environment, despite some limitations. The respondents were, for example, unwilling to engage in public demonstrations to protect the environment, despite their strong involvement in the fallist movements of 2015/16 at South African universities. There is, therefore, a need to change their perceptions about the environment, especially with regard to protecting the environment. The results of the study do, however, show that there is potential to grow the environmentalism movement among students. Environmental problems have a significant impact on humans in the same way that other social problems, such as crime, unemployment, and poverty do. The study revealed that some social issues such as crime, unemployment and poverty are considered more important than environmental issues, despite the intersecting nature of social issues with environmental issues; environmental awareness should thus be afforded the same level of recognition and importance. The findings also revealed that education plays a role in determining an individual’s level of environmental consciousness. Overall, the research confirmed some of the findings from previous similar studies. The findings confirm that the participants often do not understand the human-nature relationship. Environmental issues seem to be a low-level concern for most people, while social issues, such as unemployment, crime, and gender-based violence, are considered more worthy of governmental intervention. However, environmental issues need to be treated with the same level of urgency as other social issues, and young people should start to act as the voices of the environment.
Keywords: Environment; Environmental consciousness; Students; Environmental degradation; Environmental issues; Environmental problems; Environmentalism; Environmental education; Environmental concern